Trajectories of pain severity in juvenile idiopathic arthritis: results from the Research in Arthritis in Canadian Children Emphasizing Outcomes cohort. Issue 1 (January 2018) - Shiff, Natalie J.; Tupper, Susan; Oen, Kiem; Guzman, Jaime; Lim, Hyun; Lee, Chel Hee; Bryce, Rhonda; Huber, Adam M.; Boire, Gilles; Dancey, Paul; Feldman, Brian; Laxer, Ronald; et al.
Abstract : Abstract: We studied children enrolled within 90 days of juvenile idiopathic arthritis diagnosis in the Research in Arthritis in Canadian Children Emphasizing Outcomes (ReACCh-Out) prospective inception cohort to identify longitudinal trajectories of pain severity and features that may predict pain trajectory at diagnosis. A total of 1062 participants were followed a median of 24.3 months (interquartile range = 16.0-37.1 months). Latent trajectory analysis of pain severity, measured in a 100-mm visual analogue scale, identified 5 distinct trajectories: (1) mild-decreasing pain (56.2% of the cohort); (2) moderate-decreasing pain (28.6%); (3) chronically moderate pain (7.4%); (4) minimal pain (4.0%); and (5) mild-increasing pain (3.7%). Mean disability and quality of life scores roughly paralleled the pain severity trajectories. At baseline, children with chronically moderate pain, compared to those with moderate-decreasing pain, were older (mean 10.0 vs 8.5 years, P = 0.01) and had higher active joint counts (mean 10.0 vs 7.2 joints, P = 0.06). Children with mild-increasing pain had lower joint counts than children with mild-decreasing pain (2.3 vs 5.2 joints, P < 0.001). Although most children with juvenile idiopathic arthritis in this cohort had mild or moderate initial levels of pain that decreased quickly, about 1 in 10 children had concerning pain trajectories (chronically moderate pain and mild-increasing pain). Systematic periodic assessment of pain severity in the months after diagnosis may help identify these concerning pain trajectories early and lay out appropriate pain management plans. Focused research into the factors leading to these concerning trajectories may help prevent them. Abstract : Supplemental Digital Content is Available in the Text.Five distinct data-derived pain severity trajectories and baseline predictors of chronically moderate pain were identified in a large inception cohort of children with juvenile idiopathic arthritis.